Active single cell encapsulation using SAW overcoming the limitations of Poisson distribution. Issue 1 (10th December 2021) - Link, Andreas; McGrath, John S.; Zaimagaoglu, Mustafa; Franke, Thomas
Abstract : We present a simple microfluidic dropmaker using surface acoustic waves to enhance cell encapsulation improving single cell loading. Abstract : We demonstrate the use of an acoustic device to actively encapsulate single red blood cells into individual droplets in a T-junction. We compare the active encapsulation with the passive encapsulation depending on the number of loaded cells as well as the created droplet volumes. This method overcomes the Poisson limitation statistical loading of cells for the passive encapsulation. In our experiments we reach a single cell encapsulation efficiency of 97.9 ± 2.1% at droplet formation rates exceeding 15 Hz.